Early Detection of Common Skin Diseases, Including Leprosy: Development and Validation of an Awareness Questionnaire - Ulfah Abqari; Ulfah Abqari; Muhammad Atoillah Isfandiari; Yudhy Dharmawan; Yudhy Dharmawan; Nadhila Beladina; Janet Matani; Mursyidul Ibad; Dian Kusuma; Feby Dwirahmadi; Jan Hendrik Richardus; Ida J. Korfage (International Journal of Public Health)
ObjectivesSkin diseases account for 1.79% of the global disease burden, though their impact may be underreported due to limited research. Raising awareness about early detection is essential, but tools to measure this are scarce. This study aimed to develop and validate a questionnaire assessing community awareness and early detection of common skin diseases, including leprosy, in Indonesia.MethodsThe questionnaire was drafted in English, translated into Bahasa Indonesia, and tested for face validity, content validity, and internal consistency. A pilot test with 25 participants and a field test with 680 participants were conducted. Results were analyzed using Cronbach alpha and descriptive methods.ResultsThe final questionnaire comprised 17 questions on skin disease: common knowledge, intentions on prevention and health-seeking behavior. Validity and internal consistency were confirmed during pilot testing, and no participants in the field test reported confusion. The Cronbach alpha score exceeded 0.70, confirming strong internal consistency.ConclusionThis validated questionnaire can assess public awareness of early skin disease detection. It is available for international adaptation and may help improve early detection and prevention in Indonesia’s healthcare system.